Penerapan Metode Multi Objective Optimization by Ratio Analysis (MOORA) Dalam Rekomendasi Pembelian Sepeda Motor - Taufik Kurnialensya Kurnialensya; Eko Siswanto (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
When making a decision to purchase a motorcycle, it is necessary to consider several criteria. These include price, environmental impact, fuel consumption, design and technology, performance and power, availability of spare parts, after-sales service, warranty on spare parts and distance to the nearest service centre. This research aims to help consumers make informed decisions when buying motorbikes by using the Multi-Objective Optimisation by Ratio Analysis (MOORA) method. The MOORA method was selected because it can handle many criteria efficiently and simply, and produce very objective decisions. Nine criteria were used with four alternatives: motor A, motor B, motor C and motor D. The MOORA calculation results ranked motor C as the highest with a value of 1.90, motor B as the second highest with a value of 1.77, motor A as the third highest with a value of 1.25 and motor D as the fourth highest with a value of 1.20. This research proves that the MOORA method can effectively and accurately provide recommendations for making decisions about purchasing motorbikes with many criteria.